Analysis Income Business Food and Beverage Informal Sector in Kecamatan Tampan City Pekanbaru - Novi Ulya Sari; Shorea Khaswarina; Didi Muwardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
A development is an effort to gain the more and the better life. There are 4 indicators in gaining the development they are economic change, human resources, social inhibition and the high of life needed. A development in the development country likes Indonesia, generally more consider the development of economic sector in the hope of much progressed in production of job vacancy.There are two kinds of economic activities, they are from formal sector and informal one. Formal sector is a sector of educated people inside. The purpose of this study is to the income of the traders from food and beverage enterprises informal sector in Kecamatan Tampan City Pekanbaru and know the problems that are usually faced by food and beverage vendors informal sector businesses. This research method using purposive sampling effort sample size of 30 food and beverage businesses. Results showed revenue traders of food and beverage business is large enough to meet the needs of life and their families, while the problems faced by the traders capital, location and problems of knowledge management is still lacking. Keywords : Informal Sector, Income, Merchant Problems